2020
DOI: 10.1155/2020/4234632
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 Expression in Nasopharyngeal Carcinoma: Association with Clinicopathological Characteristics and EMT Markers

Abstract: The forkhead box (FOXA) family of transcription factors regulates gene expression and chromatin structure during tumorigenesis and embryonic development. Until now, the relationship between FOXA1 and the nasopharyngeal carcinoma (NPC) has not yet been reported. Therefore, our purpose is to analyze the expression of FOXA1 in 56 NPC patients compared to 10 normal nasopharyngeal mucosae and to correlate the expression with the clinicopathological features. Besides, we investigated the association between FOXA1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Moreover, FOXA1-over-expressing cholangiocarcinoma cells exhibit a significant reduction in proliferative, invasive and spheroid formation abilities, and its down-regulation subsequently reduces microRNA (miR)-122 expression and induces epithelial-mesenchymal transition (EMT) and disease progression 19 . In nasopharyngeal carcinoma, FOXA1 overexpression associates with a non-aggressive behavior and favorable prognosis in early TNM stages 16 , and suppresses growth, migration and invasion of the carcinoma cells via downregulation of miR-100-5p or miR-125b-5p 17 . As a tumor suppressor, FOXA1 was found to inhibit PI3K/Akt signaling pathway in hepatocellular carcinoma 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FOXA1-over-expressing cholangiocarcinoma cells exhibit a significant reduction in proliferative, invasive and spheroid formation abilities, and its down-regulation subsequently reduces microRNA (miR)-122 expression and induces epithelial-mesenchymal transition (EMT) and disease progression 19 . In nasopharyngeal carcinoma, FOXA1 overexpression associates with a non-aggressive behavior and favorable prognosis in early TNM stages 16 , and suppresses growth, migration and invasion of the carcinoma cells via downregulation of miR-100-5p or miR-125b-5p 17 . As a tumor suppressor, FOXA1 was found to inhibit PI3K/Akt signaling pathway in hepatocellular carcinoma 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the biologic role of FOXA1 has been investigated in various human cancers including the mammary 6 , 12 , 13 , prostatic 8 , 10 , hepatocellular 14 , cervical 15 , nasopharyngeal 16 , 17 and colorectal 18 carcinomas, cholangiocarcinoma 19 and ductal carcinoma in situ of the breast 20 using different methodologies, although contradictory data were obtained concerning its prognostic implications and as whether it acts as an oncogene or a tumor-suppressor gene 5 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…While the direct effects of EBV oncoproteins including LMP1 on adrenergic signaling is unclear, the study showed that both clones of the NPC cell line expressed ADRB2 and were inhibited by PRO through downregulation of MMP-2/9 expression [17]. Similarly, the forkhead box (FOXA) family of transcription factors have been implicated in the biology of NPC [53,54]. Overexpression of FOXA1 has been shown to suppress proliferation, migration, and invasion of NPC cells in culture [53].…”
Section: Targeting the Adrenergic-angiogenic Axis In Hnscc Repurposing Neuroscience Drugs-a Case For Propranololmentioning
confidence: 99%
“…Overexpression of FOXA1 has been shown to suppress proliferation, migration, and invasion of NPC cells in culture [53]. In NPC patients, FOXA1 expression has been correlated with prolonged disease-free survival and overall survival [54]. However, the effects of PRO on FOXA1 signaling has not been previously reported.…”
Section: Targeting the Adrenergic-angiogenic Axis In Hnscc Repurposing Neuroscience Drugs-a Case For Propranololmentioning
confidence: 99%
“…( Figure 1 f) FOXA1 is highly expressed in normal nasopharyngeal tissue and is downregulated in NPCs, and its overexpression can inhibit cell proliferation and invasion. This possibly occurs due to its ability to disrupt processes related to EMT, such as the inhibition of Twist1 [ 85 , 86 ].…”
Section: Epstein–barr Virus Induces Emt In Nasopharyngeal Carcinomas Through Latent Membrane Protein-1mentioning
confidence: 99%